Manganese and cobalt activate zebrafish ovarian cancer G-protein-coupled receptor 1 but not GPR4. (4th July 2017) - Negishi, Jun; Omori, Yuka; Shindo, Mami; Takanashi, Hayate; Musha, Shiori; Nagayama, Suminori; Hirayama, Jun; Nishina, Hiroshi; Nakakura, Takashi; Mogi, Chihiro; Sato, Koichi; Okajima, Fumikazu; et al.
Abstract: Mammalian ovarian G-protein-coupled receptor 1 (OGR1) is activated by some metals in addition to extracellular protons and coupling to multiple intracellular signaling pathways. In the present study, we examined whether zebrafish OGR1, zebrafish GPR4, and human GPR4 (zOGR1, zGPR4, and hGPR4, respectively) could sense the metals and activate the intracellular signaling pathways. On one hand, we found that only manganese and cobalt of the tested metals stimulated SRE-promoter activities in zOGR1-overexpressed HEK293T cells. On the other hand, none of the metals tested stimulated the promoter activities in zGPR4- and hGPR4-overexpressed cells. The OGR1 mutant (H4F), which is lost to activation by extracellular protons, did not stimulate metal-induced SRE-promoter activities. These results suggest that zOGR1, but not GPR4, is also a metal-sensing G-protein-coupled receptor in addition to a proton-sensing G-protein-coupled receptor, although not all metals that activate hOGR1 activated zOGR1.